The Effectiveness of Mindfulness Training on Reducing Aggression and Increasing the Mental Health of Soldiers - Hossein Rostami; Ayatollah Fathi; Ayaz Kheyri (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: The purpose of this study is to investigate the effectiveness of mindfulness education on decreasing aggression and increasing mental health of soldiers of the 321 armed forces of Marand Army.  Methods: The research method was semi-experimental with pretest-posttest design and control group. 30 soldiers who had higher scores in aggression and mental health tests were randomly divided into two experimental and control groups. Group training sessions were held in a weekly session during eight 90-minute sessions. Subsequently, both test and control groups were subjected to post-test implementation. Bass & Perry Aggression Questionnaire (AQ) and Goldberg & Hiller's Mental Health Questionnaire were administered to the two groups. To analyze the data, multivariate covariance test (MANCOVA) was used.  Results: Findings showed that the training of mindfulness on aggression components among military soldiers at the significant level has a significant effect (P <0.05). Mentally-mindedness education has a significant effect on the mental health components among military soldiers at the significance level of (P <0.05).   Conclusion: We concluded that the use of mind-bending techniques and teachings was effective in reducing aggression and improving mental health among soldiers.